2014
DOI: 10.1097/sla.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Mesenteric Lymph and Plasma During Acute Pancreatitis

Abstract: This study is the first to demonstrate both the presence of circulating miRNAs in lymph and the alteration of specific miRNAs in AP. Furthermore, these miRNAs alter in rat and human AP plasma and have potential to be explored as novel biomarkers of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…We observed a significant fold change (RQ: 6.4 (p ¼ 0.045)) in MAP and SAP vs. controls (RQ: 28 (p ¼ 0.03)). In the comparable study by Blenkiron et al [15] the authors failed to achieve amplification reliability of plasma miR-16 and they reported raw Ct values, without normalization. In contrast to miR-16, if we used global normalization approach, we did not observe significant variability in hsa-miR-103a-3p levels in MAP and SAP patients vs. controls (RQ: 1.1 (p ¼ 0.454) and 0.9 (p ¼ 0.099), respectively) as well as in MAP vs. SAP patients (RQ: 0.8 (p ¼ 0.291)).…”
Section: Normalization Of Selected Mirna Levelsmentioning
confidence: 88%
See 2 more Smart Citations
“…We observed a significant fold change (RQ: 6.4 (p ¼ 0.045)) in MAP and SAP vs. controls (RQ: 28 (p ¼ 0.03)). In the comparable study by Blenkiron et al [15] the authors failed to achieve amplification reliability of plasma miR-16 and they reported raw Ct values, without normalization. In contrast to miR-16, if we used global normalization approach, we did not observe significant variability in hsa-miR-103a-3p levels in MAP and SAP patients vs. controls (RQ: 1.1 (p ¼ 0.454) and 0.9 (p ¼ 0.099), respectively) as well as in MAP vs. SAP patients (RQ: 0.8 (p ¼ 0.291)).…”
Section: Normalization Of Selected Mirna Levelsmentioning
confidence: 88%
“…To improve patient diagnostics and predict outcome in AP patients, new strategies based on miRNAs have been proposed recently [15,20,21]. However, results of some clinical studies are not concordant with animal (rat) models, where different microRNAs have been selected (e.g., miR-15b, miR-16, miR-216a) [22,23].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ma X et al reported that miR-21 was overexpressed in a murine model of AP [14], and An F et al discovered that miR-24-3p, miR-361-5p, miR-1246 and miR-222-3p were constantly up-regulated, and miR-181a-5p was constantly down-regulated, in hypertriglyceridemia-induced acute pancreatitis patients [15]. Moreover, it has been reported that miR-375, miR-217, miR-148a, miR-216a, miR-122, miR-214 and miR-138 were increased in mesenteric lymph nodes from rats with AP, and miR-217, miR-375, miR-122 and miR-148a were also increased in matched rat plasma samples [16]. Though many miRNAs have been reported as biomarkers for AP, additional research is necessary regarding miR-155-5p, which is involved in chronic inflammation caused by adipose tissue [17], and whose role in the development of AP is still not clear.…”
Section: Introductionmentioning
confidence: 96%
“…Microarray is based on the hybridization of nucleic acids on different supports and for its less sensitivity, generally requires a higher RNA input (100 ng1ug) that probably represents the major limitation of this application. Moreover, it can often be difficult to discriminate mature from immature miRNAs forms due to background and cross-hybridization issues [35,36]. The recent introduction of deep sequencing miRNAs (miRNA-seq), a NGS approach, allowed not only to assess miRNA expression levels but also to identify unknown miRNAs.…”
Section: Circulating Micrornamentioning
confidence: 99%